VIOLENCE AGAINST WOMEN FROM THE VIEW OF HUMAN RIGHTS (CIPEEX, 2022)
THIS ARTICLE AIMS TO ANALYZE VIOLENCE IN ITS PHYSICAL, MORAL AND PSYCHIC TERMS AND ALSO DISCUSS THE INTRODUCTION OF THE MARIA DA PENHA LAW IN BRAZIL, THE TYPES OF VIOLENCE ESTABLISHED BY THE LAW AND THE CONSEQUENCES GENERATED IN THE LIVES OF THE CHILDREN PRESENT AT THE TIME. OF DOMESTIC VIOLENCE. IN ADDITION, THE ARTICLE WILL DEAL WITH GENDER INEQUALITY BETWEEN MEN AND WOMEN IN SOCIETY, MEANS OF PROTECTING WOMEN, TARGETING THE PROFILE OF THE AGGRESSOR, AND THE VIOLATION OF HUMAN RIGHTS TOWARDS THE VICTIM. DOMESTIC VIOLENCE ENCOMPASSES MUCH MORE THAN A MAN ASSAULTING A WOMAN, THE ARTICLE AIMS TO REPORT AND CLARIFY WHAT HAPPENS TO THESE WOMEN.
Keywords: Domestic violence; Inequality; Voltage